Kebijakan Hukum Terhadap Tindak Pidana Child Grooming - Dessy Lina Oktaviani Suendra; Kade Richa Mulyawati (Kertha Wicaksana, 2020)
The rapid community gathering followed by the rapid advancement of technology with the internet not only brought positive but also tucked in negatively, one of which developed developing follow-up section on the abuse of children called child care carried out by using internet technology which is increasingly becoming a necessity the main community. Child care unwittingly began to occur in Indonesia, began to emerge several cases discussed are child care. The emergence of this new criminal act is not accompanied by supporting legal instruments as evidenced by the absence of special agreement relating to this crime requiring legal officers who find difficulties in processing child care cases that have been carried out. The only way for the police to take discretion is to be able to sentence the victim. The method used in this renewal is a method that is approved by juridical normative using the Statute Approach which uses literature and legislation relating to the topics discussed. Child grooming crime is still classified as a criminal new offense in Indonesia so that there are no specific regulations related to it. So that perpetrators of these crimes can still be held accountable for their actions, law enforcement officials take the policy of discretion as a way out of this.